Educating a new generation of nurses about workplace violence using an innovative virtual simulation module - Brandau, Melvina; Lloyd, Brianna (American Journal of Education and Learning, 2024)
Workplace violence (WPV) continues to be a pervasive and burdensome issue. Nurses spend more time with patients and families increasing their WPV risk. Unfortunately, nursing programs do not routinely provide education or training on de-escalation or management of WPV. Future and current nurses should acknowledge and receive education for the prevention and mitigation of WPV as well as frequent reviews and updates on current trends and strategies. The purpose of this study was to evaluate the impact of education on knowledge of WPV among pre-nursing students at a Midwestern university. This study used a pre-and post-tests, quasi-experimental design with 99 students. A brief knowledge test was completed by participants both before and after the intervention. Pre- and post-test scores were collected across sections. Analysis of paired sample t-tests demonstrated a 20% average increase in post-test scores with a statistically significant increase from pre-test scores (t=-11.357, p<0.001). Results indicated that the innovative, virtual simulation module increased participants’ knowledge of workplace violence in healthcare. Increased knowledge of and preparation for the WPV workplace would strengthen students’ safety readiness for practice with the persistence of WPV against nurses. Prevention and response of WPV education must be an essential component of every undergraduate nursing program following licensure.